Measurement accuracy analysis for microgeometry nanostandards with microinterferometer and stylus profilometer - Łukasz Ślusarski (Biuletyn Wojskowej Akademii Technicznej, 2018)
The goal of the work, described in this paper, was to examine and analyse measurement capabilities of GUM Length and Angle Department in measurements of step height/depth standards with the values below 1 μm (nanostandards), with 2D, and 3D surface characteristics. Measurements were performed with microinterforometer and stylus profilometer. Keywords: nanometrology, depth/height standards, microinterferometry, contact profilometry.